Editorial - Dilnawaz A. Siddiqui (International Institute of Islamic Thought, 2005)
This issue coincides with several momentous events and trends in the world at large and Muslim nations. The heads or top representatives of the 57 Muslimmajority nations have held an extraordinary meeting at Makkah under the Organization of Islamic Conferences’ (OIC) aegis. A major goal is to reactivate and empower the OIC so that it can actively help the ummah deal with its huge opportunities and challenges. Several salient issues were stressed: the need for closer interaction, collaboration, and internal reform leading to a peaceful, pluralistic, and moderate disposition of Islam and Muslims. Muslim nations are trying to address their internal weaknesses and build upon their strengths. In terms of human and material resources, the Muslim world is composed of three kinds of countries: those with large populations and poor economies, small populations and rich economies, and with both fairly large populations backed by rich economic resources. They seem to believe that Iraq and Iran, the very backbone of the third category, are currently targeted for long-term occupation. They are exploring how to compensate for one another’s drawbacks and reinforcing their assets. The OIC declaration, hailed as a historic turning point, stresses that Muslims take responsibility for their present plight and stop blaming others. In addition, the organization will be renamed, get a new charter, and be run by mandatory contributions from member nations. It will also feature conflict- resolution and consensus-building mechanisms to resolve both minor and major conflicts, such as Palestine and Kashmir. The ummah and the world now wait to see whether such statements are more than rhetoric. Concurrently, there is an increasing awareness of the futility of cardinaldirectional conflicts and the “clash of civilizations” between the West and the East, or between the North and the South. Ever more Muslim and other intellectuals realize that the real confrontation is between powerful global forces of greed and exploitative profiteering on the one hand, and people of candor, conscience, and moral orientation on the other. Among the individuals and organizations in the latter camp, there is growing realization of the need for societal reform toward pluralism, learning from each other, collective and consultative decision making, basic freedoms for all, peace with justice, and institution building that is compatible with the speed, complexity, and magnitude of the emerging globalized world ...